Jiangella endophytica sp. nov., an endophytic actinomycete isolated from the rhizome of Kaempferia elegans - Nantawan Niemhom; Chanikul Chutrakul; Chanwit Suriyachadkun; Sarin Tadtong; Chitti Thawai (My University, 2018)
An endophytic actinobacterium, designated strain KE2-3T, was isolated from surface-sterilised rhizome of Kaempferia elegans. The polyphasic approach was used for evaluating the taxonomic position of this strain. The taxonomic affiliation of this strain at genus level could be confirmed by its chemotaxonomic characteristic, i.e. the presence of ll-diaminopimelic acid in the cell peptidoglycan, MK-9(H4) as the major menaquinone, iso-C16 : 0, anteiso-C15 : 0, iso-C14 : 0 and iso-C15 : 0 as the predominant fatty acids in cells, and the presence of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol and phosphatidylinositol mannoside in its membranes. Based on 16S rRNA gene sequence analysis, strain KE2-3T was identified as a member of the genus Jiangella and showed the highest similarities to Jiangella muralis DSM 45357T (99.3 %) followed by Jiangella albaDSM 45237T (99.2 %), Jiangella alkaliphilia DSM 45079T (99.0 %), Jiangella gansuensisDSM 44835T (98.8 %) and Jiangella mangrovi3SM4-07T (98.6 %). However, the draft genome sequence of strain KE2-3T exhibited low average nucleotide identity values to the reference strains (85.5-90.2 %), which were well below the 95-96 % species circumscription threshold. The DNA G+C content of genomic DNA was 72.3 mol%. With the differences of physiological, biochemical and genotypic data, strain KE2-3T could be discriminated from its closest neighbour. Thus, strain KE2-3T should be recognised as a novel species of genus Jiangella, for which the name Jiangellaendophytica sp. nov. is proposed. The type strain is KE2-3T (=BCC 66359T=NBRC 110004T).
Keywords: Strain (injury); Diamino acid; genomic DNA; Genomics and Phylogenetic Studies